A revision of the family Protorchestiidae (Amphipoda: Talitroidea) with the description of two new subfamilies, three new genera and one new species - Myers, Alan A.; Park, Eunji; Ball, Olivier J.-P. (Zootaxa, 2025)
Amphipods have successfully adapted to a wide range of environments, including marshes. The family Protorchestiidae comprises a diverse group of marshhoppers; however, its classification has been challenging due to subtle morphological differences among genera. In this study, the family Protorchestiidae is revised, and two new subfamilies are erected. Microrchestiinae subfam. nov. is tropical to subtropical in distribution, Protorchestiinae subfam. nov. inhabits cold to cool-temperate regions. The two new subfamilies are diagnosed and their distributions are reviewed. Three new genera, Lowryorchestia gen. nov., Richardsonorchestia gen. nov. and Serejorchestia gen. nov., are described from New Zealand and Australia. These new genera are most similar to Protorchestia that is endemic to South America and probably also to the poorly known Eorchestia that is endemic to South Africa. One new species, Lowryorchestia riparicola gen. nov., sp. nov. is described from New Zealand. Neorchestia plicibrancha Friend, 1987 is regarded as incertae sedis.